Credit rating agencies: Part of the solution or part of the problem? - Gunther Tichy; Karel Lannoo; Owain Ap Gwilym; Rasha Alsakka; Donato Masciandaro; Bartholomew Paudyn (Intereconomics, 2011)
Credit rating agencies have come under increased scrutiny since the financial crisis. Their failure to recognise the threats to the financial system prior to the crisis coupled with their steady downgrading of European sovereign debt has led to much criticism, especially from European politicians and economists. This Forum examines the major agencies' influence, independence and performance and explores whether a publicly funded European agency would improve the situation.
Keywords: 330